'Is little to be gained by lamenting the past?' : Assessing the extent to which addressing the past legacy of the South African and Kenyan judiciaries by means of transitional justice mechanisms, has contributed to achieving the objectives of judicia - Boast, Jessica (Department of Political Studies, 2014)
The purpose of this dissertation is to determine whether it is important for the future development of legal systems in post-authoritarian or post-conflict states to confront the unjust past legacy of their judiciaries. In order to determine this, one has to assess the extent to which addressing the unjust past legacy of such judiciaries, by means of transitional justice mechanisms, has contributed to achieving the objectives of judicial reform is these contexts. This is accomplished by firstly, analysing the contribution of the TRC Legal Hearing to judicial reform in post-Apartheid South Africa. Secondly, the contribution which the vetting of the Kenyan judiciary made to achieving judicial reform in Kenya after the 2007 Election crisis is assessed. In both circumstances, the final contributions of these transitional justice mechanisms to achieving the objectives of judicial reform are weighed against the contributions of other mechanisms. It is argued that both the transitional justice mechanisms of truth commissions and judicial vetting contributed to achieving objectives of judicial reform in South Africa and Kenya. However, the extent of the contributions differed in each case because of unique political factors. It is concluded that confronting the unjust past legacy of judiciaries in post-authoritarian and post-conflict states is indeed important for the future development of their legal systems.